Presentation: The SceSam Project: Interactivity in Children´s Theatre - Nagel, Lisa; Hovik, Lise (BUKS - Tidsskrift for Børne- & Ungdomskultur, 2016)
SceSam is an artistic research project (2012-15) in which we have examined interactivity in performances for children (age 3-9) through theory and practice (Nagel and Hovik 2015). Organized as a team of researchers in a research group, practitioners and theoreticians have explored the complex landscape of interactive theatre for children through performances, in seminars, in workshops and in articles. Together with mentors from SceSam, four different artist/companies have developed their own interactive performances, researching different aspects of the performers´ relationships with the child audiences in workshops. Lisa Nagel is the artistic leader of the project, which she has developed together with fellow researcher Lise Hovik and producer Hege Knarvik Sande.